PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN (PNPM-MPD) DI KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS TAHUN 2012 - Nian E.21109067, Tegar (FISIP Universitas Tanjungpura, 2013)
The aim of this research is to given an understanding about the implementation to resolve the problems of the low poor participation in implementation of PNPM-MPd that have been implemented in District Teluk Keramat. The problems about the low poor participation that have been happened in District Teluk Keramat was give anxiety to investigate that many people who are less participates in the implementation of PNPM-PMd. The purpose of this research also to make the process of the implementation of PNPM-PMd can be happen according the purpose of a program that refers to increasing of the low poor participation ,until the poor can be helped in terms of employment opportunities. The implementation of PNPM-MPd in District Teluk Keramat Regency Sambas. The research method used is descriptive with the technique of data qualitative analysis. This study includes three terms in conduct of the research that are organizing , interpretation and application. The results showed that implementation of PNPM-PMd in District Teluk Keramat Regency Sambas is not maximized. That is because the inhibiting factor of the quality of human resources is uneven and disobedience to estabilished procedures of prioritize of the poor. Keywords: implementation , policy, PNPM-MPd